Sport, theory and social problems a critical introduction - Anderson, Eric 1968-; White, Adam (Routledge, Taylor & Francis Group, 2017)
In a revised, updated, and considerably expanded new edition of Sport, Theory and Social Problems, authors Eric Anderson and Adam White examine how the structure and culture of sport promotes inequality, injury, and complicity to authority at the non-elite levels of play in Anglo-American countries. By introducing students to a research-led perspective on sport, it highlights the operation of power, patriarchy, and pain that a hyper-competitive sporting culture promotes. Each chapter includes at least one key social theory, which is made accessible and pragmatic. The theory is then infused throughout the chapter to help the student engage with a deeper understanding of sport. In addition to examining how sport generates otherness, distracts children from education, and teaches the acceptance of emotional and physical violence, this new edition also examines how organized, competitive sport divides us by race, denies children the right to their own governance, and promotes brain trauma and chronic traumatic encephalopathy in those who are too young to consent to play contact sports. It is an essential textbook for any sport studies degree with a focus on the sociology of sport, sport and social theory, children's health and well-being, or sport and gender studies.